REAKTUALISASI KONSEP ‘ADAB’ DALAM PENDIDIKAN ISLAM: STUDI KOMPARATIF KRITIS PEMIKIRAN SYED MUHAMMAD NAQUIB AL-ATTAS DAN M. AMIN ABDULLAH - Muh. Ramadhan; Mukmin; Faisal, Andi; Musdalifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to critically compare the conceptualization of ‘adab’ in Islamic education according to Syed Muhammad Naquib al-Attas and M. Amin Abdullah. Using a qualitative approach with critical literature study design, this research analyzes the epistemological, methodological, and practical differences between the two thinkers. The results show that al-Attas positions ‘adab’ as a metaphysical-cosmological foundation that restores the hierarchical order of knowledge and existence, while Abdullah reconstructs ‘adab’ as an integrative-interconnective ethics capable of dialoguing with plural and fragmented contemporary knowledge. Although both place ‘adab’ as the heart of transformative education, their approaches differ in source of authority, methodology, and orientation. This study offers a dialectical synthesis of both paradigms, proposing ‘adab’ as an epistemic compass in the digital era, a foundation for inclusive identity, and holistic ecological ethics. The research concludes that the reactualization of ‘adab’ requires a combination of strong metaphysical foundations (al-Attas) and flexible contextual methodologies (Abdullah) to address contemporary challenges without losing Islamic identity. Keywords: Adab, Syed Muhammad Naquib Al-Attas, M Amin Abdullah, Islamic Education, Comparative Study, Integration-Interconnection, Islamization of Knowledge.